LGBT advocacy on twitter : cultivating exposure and perception of Muslim users and the challenges towards islamic morality - Nurliyana Mohd Noor (International Institute of Islamic Thought and Civiiisation, International Islamic University Malaysia, 2021)
LGBT issues are gaining attention in Malaysia due to escalating portrayals of advocacy contents on social media. Multiple case studies in the United States have proven how social media engagements and interactions has led to acceptance by the general public. Virtual platforms have provided most conducive space and practical tools for self-identification, coming out and advocacy activities. While multiple studies have investigated Facebook as a medium to convey advocacy messages, there have been very few studies on how Twitter could play the same role. Thus, this study intends to unravel how users’ perceptions can be shaped through continuous advocacy initiatives on Twitter, specifically of how the Malaysian Muslim Twitter users’ perceptions are shaped through exposure to LGBT advocacy contents on the social media platform. The research instrument employed is quantitative, and the variables include perception of users towards advocacy activities, perception of users towards the prevalence of advocacy contents and exposure to advocacy contents. The outcome of this research shows confirmation in terms of users’ encounter with LGBT related contents through their experience of being Twitter users and the agreement of being exposed to a lot of LGBT contents through the platform.